2017
DOI: 10.4236/ojg.2017.712122
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Adsorption and Desorption Properties of Marine Shales on Longmaxi Shale in South China

Abstract: The investigation of adsorption and desorption properties of shale are important for estimating reserves and exploitation. The shale samples used in this paper were from the marine shale on Longmaxi shale in Sichuan and Hubei province, China. A series of analyses, such as organic carbon content test, vitrinite reflectance test, rock pyrolysis, X-ray diffraction, and N 2 /CO 2 adsorption were performed. Gravimetric method with magnetic suspension balance was used to conduct isothermal adsorption and desorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The experimental investigation suggested that higher temperature results in a lower gas sorption content in the Devonian shale reservoir . Zhang believed that methane adsorption in both shale and isolated kerogen decreased with increasing temperature, which is in line with the conclusions obtained from other investigations. It is widely reported that methane excess adsorption in shale and coal does not increase monotonically but first increases and then decreases with increasing pressure. ,, However, the absolute adsorption increases monotonically and is greater than the excess adsorption. , The difference between absolute adsorption and excess adsorption is related to the ratio of the free gas density to the adsorbed gas density. , The density of free gas in the low-pressure stage is much lower than the density of adsorbed gas; therefore, the excess adsorption is approximately equal to the absolute adsorption. With the increase of pressure, when the increasing rates of the free gas density and the adsorbed gas density are equal, the excess adsorption reaches the maximum .…”
Section: Introductionsupporting
confidence: 65%
“…The experimental investigation suggested that higher temperature results in a lower gas sorption content in the Devonian shale reservoir . Zhang believed that methane adsorption in both shale and isolated kerogen decreased with increasing temperature, which is in line with the conclusions obtained from other investigations. It is widely reported that methane excess adsorption in shale and coal does not increase monotonically but first increases and then decreases with increasing pressure. ,, However, the absolute adsorption increases monotonically and is greater than the excess adsorption. , The difference between absolute adsorption and excess adsorption is related to the ratio of the free gas density to the adsorbed gas density. , The density of free gas in the low-pressure stage is much lower than the density of adsorbed gas; therefore, the excess adsorption is approximately equal to the absolute adsorption. With the increase of pressure, when the increasing rates of the free gas density and the adsorbed gas density are equal, the excess adsorption reaches the maximum .…”
Section: Introductionsupporting
confidence: 65%
“…Several factors contributing to the adsorption amount have been reported to date (for example, ref ). According to previous experimental studies, total organic carbon (TOC), thermal maturity, and clay content ,, are positively correlated with the adsorption amount, while temperature and moisture content , have a negative correlation with the adsorption amount.…”
Section: Introductionmentioning
confidence: 92%